Sixteen in One: White-Belted Megaselia Rondani (Diptera: Phoridae) From the New World Challenge Species Concepts. Issue 3 (9th May 2022) - Brown, Brian V; Hartop, Emily A; Wong, Maria A
Abstract: We review the species of Megaselia similar to Megaselia sulphurizona Borgmeier. A close examination of M. sulphurizona indicates that its current concept includes at least 16 species, 15 of which— Megaselia albizona, Megaselia borealizona, Megaselia colombizona, Megaselia cryptizona, Megaselia danizona, Megaselia guanizona, Megaselia marizona, Megaselia nivizona, Megaselia oklizona, Megaselia paulizona, Megaselia reductizona, Megaselia solizona, Megaselia tropizona, Megaselia wendizona, and Megaselia winnizona are described as new, based primarily on molecular data. The identity of the holotype of the species M. sulphurizona is clarified through wing vein morphometrics. Two of the new species, M. albizona and M. cryptizona, are the 47 th and 48 th new species of phorid fly described from the BioSCAN project, an urban biodiversity study in Los Angeles, California, U.S.